Tales from Du Bois : the queer intimacy of cross-caste romance - Williams, Erika Renée, 1973- (Albany : State University of New York Press, 2022)
"Offers a new framework for understanding Du Bois's poetics and politics, including the concept of double consciousness, by tracing the trope of the cross-caste romance across his fiction"--
Introduction: On double consciousness as the failure of cross-caste romance : Du Bois’s nationalism re- and de-formed -- A hymn of faith is a tale of love : Lohengrin and platonic romance in Du Bois’s “Of the coming of John” -- The queer gift of Black folk : reading double consciousness in Du Bois’s detective fiction -- A romance of refusal : failed intimacy and Black fugitivity in “The princess of the Hither Isles” -- Crossing caste and queering kinship : Du Bois’s utopian Afro-Asiatic romance -- Epilogue: Strange intimacies : on exogamy and endogamy in the cross-caste romance.
Includes bibliographical references (pages 145-152) and index.
Print version record.
JSTOR
Keywords: Du Bois, W. E. B. -- 1868-1963 -- Criticism and interpretation; Du Bois, W. E. B. -- 1868-1963; Interracial couples in literature; Caste in literature; Couples mixtes dans la littérature.; Castes dans la littérature.; LITERARY CRITICISM / American / African-American.; Caste in literature; Interracial couples in literature; Criticism, interpretation, etc